Ausencia de la figura paterna en el desarrollo psicológico del niño - Sari Masache, Cristian Fernando (2024)
This literature review paper is aimed to comprehensively examine the impact of Father Absence on Child Psychological Development in Central and South American countries. Its main objective is to explore in a detailed and systematic way how the absence of a paternal figure affects the cognitive, emotional, social and behavioural well-being of children in these regions. To perform this review, for which we used a mixed approach combining qualitative and quantitative methods, 17 documents selected from an initial population of 133 sources were analysed and synthesised, applying rigorous inclusion and exclusion criteria and the PRISMA protocol to ensure the relevance and quality of the analysis. The results of this literature review indicate a clear association between paternal absence and a range of adaptive disorders in children, including deficits in cognitive and psychomotor development, impulsivity, illicit substance use, behavioural problems, and emotional difficulties such as anxiety, stress, mood disturbances and sleep deprivation. This finding underscores the urgent need to design and implement effective intervention measures and provide support to affected families to mitigate the adverse effects that this deprivation can have on children's overall development and well-being